2021
DOI: 10.17645/si.v9i2.3837
|View full text |Cite
|
Sign up to set email alerts
|

Housing Vienna: The Socio-Spatial Effects of Inclusionary and Exclusionary Mechanisms of Housing Provision

Abstract: The provision of housing plays a decisive role in segregation processes. In a European context increasingly influenced by variegated neo-liberal housing policies, Vienna’s approach is characterised by generous access to social housing. This inclusive strategy aims at actively preventing segregation and the isolation of certain groups. Over the last 30 years, however, reconfigured multi-level arrangements and wider contextual changes have transformed Vienna’s housing governance. This article explores how. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Despite the city's temporary withdrawal as a housing developer, rent subsidies were retained and the construction of apartments remained subsidised by the city for instance with so-called 'Housing Initiatives' (Hatz et al, 2016). The shift from constructing municipal housing to subsidising social housing affected the inclusionary mechanisms as tenants in the non-profit housing sector typically have to pay down-payments while tenants in council housing do not (Friesenecker and Kazepov, 2021). The city currently plans to build roughly 4300 new municipal flats by 2025 which is probably too little to keep up the share of council housing in the housing stock (Kadi et al, 2021).…”
Section: A Brief History Of Council Housing In Viennamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the city's temporary withdrawal as a housing developer, rent subsidies were retained and the construction of apartments remained subsidised by the city for instance with so-called 'Housing Initiatives' (Hatz et al, 2016). The shift from constructing municipal housing to subsidising social housing affected the inclusionary mechanisms as tenants in the non-profit housing sector typically have to pay down-payments while tenants in council housing do not (Friesenecker and Kazepov, 2021). The city currently plans to build roughly 4300 new municipal flats by 2025 which is probably too little to keep up the share of council housing in the housing stock (Kadi et al, 2021).…”
Section: A Brief History Of Council Housing In Viennamentioning
confidence: 99%
“…Social housing popped up across the city and was not limited to specific low-income neighbourhoods. The era of Red Vienna ended with the political rise of fascism in 1934, but the construction of social housing accelerated after World War II and its provision remained a key element of Viennese welfare policies (Friesenecker and Kazepov, 2021; Kadi, 2015).…”
Section: A Brief History Of Council Housing In Viennamentioning
confidence: 99%
“…Debates broaching transitions of housing markets, in general, have become well-represented in academic discourses, also for the example of Vienna (for ongoing debates, see Aigner, 2020;Friesenecker & Kazepov, 2021;Gruber & Franz, 2019;Kadi et al, 2021;Kohlbacher & Reeger, 2020;Musil et al, 2022). However, discussions about eroding or missing social housing policies for institutional student housing and its implications for social infrastructure provision remain under-represented.…”
Section: Introductionmentioning
confidence: 99%
“…The potential consequences for students as a vulnerable group (see Berglund-Snodgrass et al, 2021) remain underresearched, though. As Vienna is renowned internationally for inclusive social housing policies (Marquardt & Glaser, 2020) and an affordable local housing market contributing to social mix (Friesenecker & Kazepov, 2021), the exemplifying case of Vienna raises general awareness of shifting outcomes in social infrastructure provision, which might cause a decline in sociality and living quality at the local level.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on socio-economic segregation in European capital cities (Tammaru et al, 2015) revealed that even though the levels of segregation in Europe are still relatively low compared with other parts of the world, ‘the spatial gap between poor and rich is widening’ (Marcińczak et al, 2015b: 358). The rapidly growing body of literature on social polarisation and increasing residential segregation (Friesenecker and Kazepov, 2021; Haandrikman et al, 2021; Hamnett, 2021; Hedberg and Tammaru, 2013; Maloutas, 2012; Maloutas and Botton, 2021a; Ouředníček et al, 2015; Tammaru et al, 2015, 2021; Van Ham et al, 2020, 2021) indicates the assumed social impacts of segregation.…”
Section: Introductionmentioning
confidence: 99%